2015
DOI: 10.1007/s11557-015-1034-2
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the diversity of European Caliciopsis (Coryneliaceae, Ascomycota): Caliciopsis valentina sp. nov. and C. beckhausii comb. nov., with a worldwide key to Caliciopsis

Abstract: Unravelling the diversity of EuropeanPostprint del artículo publicado en: Mycological Progress 14: 1-11 (2015) AbstractThe new species Caliciopsis valentina from the eastern Iberian Peninsula is characterized morphological, anatomical and molecularly. The occurrence of C. subcorticalis (Cooke & Ellis) Fitzp. in Europe is discussed. Based on the revision of fresh and herbarium specimens we propose the new combination Caliciopsis beckhausii with a neotype selected for this taxon. New molecular data (nrITS and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…A basal frill, the remnant of the bitunicate wall, may occur at the base of mature asci ( Johnston & Minter 1989 ). This same ascus morphological development was observed for all species examined in this study, and was also observed in the recently described Caliciopsis beckhausii and C. valentina ( Garrido-Benavent & Pérez-Ortega 2015 ). In some genera of the Sordariales ( Jattaea , Pleurostoma , and Togninia ) that are not closely related to typical bitunicate fungi, so-called remnant bases remain on the ascogenous hyphae after detachment of mature, undamaged asci, or hair-like structures were observed at the bases of asci that are reminiscent of the frills at the ascus base of Coryneliomycetidae ( Réblová et al 2004 , Mostert et al 2006 , Damm et al 2008a , b ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A basal frill, the remnant of the bitunicate wall, may occur at the base of mature asci ( Johnston & Minter 1989 ). This same ascus morphological development was observed for all species examined in this study, and was also observed in the recently described Caliciopsis beckhausii and C. valentina ( Garrido-Benavent & Pérez-Ortega 2015 ). In some genera of the Sordariales ( Jattaea , Pleurostoma , and Togninia ) that are not closely related to typical bitunicate fungi, so-called remnant bases remain on the ascogenous hyphae after detachment of mature, undamaged asci, or hair-like structures were observed at the bases of asci that are reminiscent of the frills at the ascus base of Coryneliomycetidae ( Réblová et al 2004 , Mostert et al 2006 , Damm et al 2008a , b ).…”
Section: Discussionsupporting
confidence: 90%
“…These characters distinguish the Coryneliales from all other members of the Euryotiomycetidae ( Eurotiales , Onygenales ). The Coryneliaceae currently contains seven genera: Corynelia (7 species), Lagenulopsis (1), Tripospora (4) ( Catania & Romero 2001 ), Caliciopsis (29) ( Garrido-Benavent & Pérez-Oriega 2015 ), Coryneliopsis (2), Coryneliospora (2), and Fitzpatrickella (1) ( www.indexfungorum.org , www.mycobank.org ), of which the first three mentioned are obligate parasites only recorded on members of the Podocarpaceae . Johnston & Minter (1989) suggested that Coryneliopsis (on Cyttaria galls on Nothofagus ) does not belong to this family, and Benny et al (1985b) excluded Corynelia sydowii .…”
Section: Introductionmentioning
confidence: 99%
“…calicioides ), ascospores ellipsoidal to subglobose or ovoid (except C . indica ) with smooth walls (Fitzpatrick, 1942b; Garrido‐Benavent & Pérez‐Ortega, 2015; Migliorini et al, 2020; Pratibha et al, 2010). Because the genus Hypsotheca has only recently been resurrected and one of its species, Hypsotheca eucalyptorum , was described only from culture, the description of morphological characteristics for this genus is limited, especially regarding the sexual morph.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors showed that species of Caliciopsis that had not had their identity confirmed by DNA sequence data might not actually belong to the genus, and thus, their morphology may not be representative of the genus. If only the nine species confirmed as Caliciopsis by sequence data are taken into account (Table 3), the common morphological traits are ascomata over 1 mm tall (except for C. indica and C. moriondi), with the ascigerous swelling terminal to subterminal (except C. calicioides), ascospores ellipsoidal to subglobose or ovoid (except C. indica) with smooth walls (Fitzpatrick, 1942b;Garrido-Benavent & Pérez-Ortega, 2015;Migliorini et al, 2020;Pratibha et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Notes — The genus Caliciopsis belongs to the Coryneliaceae ( Coryneliales , Coryneliomycetidae ) ( Wood et al 2016 ), and has phoma-like asexual morphs ( Garrido-Benavent & Pérez-Ortega 2015 ). Phylogenetically, C. eucalypti is related to but distinct from C. beckhausii (conidia 3.5–4.5 × 1–1.5 μm; ITS GenBank KP144005, Identities = 538/581 (93 %), Gaps = 19/581 (3 %)), C. calicioides (conidial dimensions unknown; ITS GenBank JX968549; Identities = 547/596 (92 %), Gaps = 20/596 (3 %)) and C. valentina (conidia 4–5 × 1–1.5 μm; ITS GenBank KP144008; Identities = 490/527 (93 %), Gaps = 17/527 (3 %)) ( Garrido-Benavent & Pérez-Ortega 2015 ) and has smaller conidia.…”
mentioning
confidence: 99%